Plasmodium falciparum parasites with histidine-rich protein 2 (pfhrp2) and pfhrp3 gene deletions in two endemic regions of Kenya. Issue 1 (December 2017) - Beshir, Khalid; Sepúlveda, Nuno; Bharmal, Jameel; Robinson, Ailie; Mwanguzi, Julian; Busula, Annette; Boer, Jetske; Sutherland, Colin; Cunningham, Jane; Hopkins, Heidi
Abstract Deletions of thePlasmodium falciparum hrp2 andhrp3 genes can affect the performance of HRP2-based malaria rapid diagnostic tests (RDTs). Such deletions have been reported from South America, India and Eritrea. Whether these parasites are widespread in East Africa is unknown. A total of 274 samples from asymptomatic children in Mbita, western Kenya, and 61 genomic data from Kilifi, eastern Kenya, were available for analysis. PCR-confirmed samples were investigated for the presence ofpfhrp2 andpfhrp3 genes. In samples with evidence of deletion, parasite presence was confirmed by amplifying three independent genes. We failed to amplifypfhrp2 from 25 of 131 (19.1%) PCR-confirmed samples. Of these, only 8 (10%) samples were microscopic positive and were classified aspfhrp2 -deleted. Eight microscopically-confirmedpfhrp2 -deleted samples with intactpfhrp3 locus were positive by HRP2-based RDT. In addition, one PCR-confirmed infection showed a deletion at thepfhrp3 locus. One genomic sample lackedpfhrp2 and one lackedpfhrp3 . No sample harbored parasites lacking both genes. Parasites lackingpfhrp2 are present in Kenya, but may be detectable by HRP-based RDT at higher parasitaemia, possibly due to the presence of intactpfhrp3 . These findings warrant further systematic study to establish prevalence and diagnostic significance.